2017
DOI: 10.5204/mcj.1283
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Term: Can Feminism Look beyond the Global North/Global South Geopolitical Paradigm?

Abstract: Introduction The genealogy of Feminist Standpoint Theory in the 1970s prioritised “locationality”, particularly the recognition of social and historical locations as valuable contribution to knowledge production. Pioneering figures such as Sandra Harding, Dorothy Smith, Patricia Hill Collins, Alison Jaggar, and Donna Haraway have argued that the oppressed must have some means (such as language, cultural practices) to enter the world of the oppressor in order to access some understanding of how the world works … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Adherence to Western publication norms and English-language dominance, along with an interest in studying in Western institutions, can inadvertently reinforce Global North intellectual dominance (Das, 2017;Glück, 2018;Keim, 2014). For instance, Ganter and Ortega (2019) and Mutsvairo et al (2021) found that Latin American researchers are more inclined to publish in English using Western frameworks rather than indigenous approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to Western publication norms and English-language dominance, along with an interest in studying in Western institutions, can inadvertently reinforce Global North intellectual dominance (Das, 2017;Glück, 2018;Keim, 2014). For instance, Ganter and Ortega (2019) and Mutsvairo et al (2021) found that Latin American researchers are more inclined to publish in English using Western frameworks rather than indigenous approaches.…”
Section: Discussionmentioning
confidence: 99%